2006
DOI: 10.1073/pnas.0601416103
|View full text |Cite
|
Sign up to set email alerts
|

The BMAL1 C terminus regulates the circadian transcription feedback loop

Abstract: The circadian clock is driven by cell-autonomous transcription͞ translation feedback loops. The BMAL1 transcription factor is an indispensable component of the positive arm of this molecular oscillator in mammals. Here, we present a molecular genetic screening assay for mutant circadian clock proteins that is based on real-time circadian rhythm monitoring in cultured fibroblasts. By using this assay, we identified a domain in the extreme C terminus of BMAL1 that plays an essential role in the rhythmic control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
135
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(142 citation statements)
references
References 28 publications
(34 reference statements)
5
135
0
Order By: Relevance
“…1D), substantially weakened the BiFC between BMAL1 and CBP, whereas overexpression of CLOCK strengthened the signal (Y.L., unpublished data). Intriguingly, the BMAL1 C-terminal domain was found to also associate with CRY1, a potent repressor of the CLOCK-BMAL1 heterodimer, thereby suppressing its target gene transcription (Kiyohara et al, 2006;Sato et al, 2006). These findings present the possibility that the BMAL1 C-terminal has antagonistic dual functions and serves as a molecular switch for the gene transcription controlled by the CLOCK-BMAL1 heterodimer.…”
mentioning
confidence: 74%
“…1D), substantially weakened the BiFC between BMAL1 and CBP, whereas overexpression of CLOCK strengthened the signal (Y.L., unpublished data). Intriguingly, the BMAL1 C-terminal domain was found to also associate with CRY1, a potent repressor of the CLOCK-BMAL1 heterodimer, thereby suppressing its target gene transcription (Kiyohara et al, 2006;Sato et al, 2006). These findings present the possibility that the BMAL1 C-terminal has antagonistic dual functions and serves as a molecular switch for the gene transcription controlled by the CLOCK-BMAL1 heterodimer.…”
mentioning
confidence: 74%
“…Physical Interaction of PER2 with BMAL2 Is Stronger than That with BMAL1-PER2 is known to interact with BMAL1 (42,43), whereas the intimate functional linkage between PER2 and BMAL2 (Fig. 5) suggested that PER2 may associate with BMAL2 more efficiently than with BMAL1.…”
Section: Bmal2 Is Less Sensitive Than Bmal1 To Repression By Crys Butmentioning
confidence: 96%
“…5 A and B). The BMAL1-DN, which lacks the Cterminal region of BMAL1 protein, strongly suppresses the BMAL1/CLOCK-mediated transcription (28). To confirm the effect of BMAL1-DN on the endogenous clock genes in somatic cells, we analyzed the expression levels of endogenous clock genes before and after the expression of BMAL1-DN in NIH 3T3 cells.…”
Section: Expression Of Clock Genes In Es Cells Ips Cells and Differmentioning
confidence: 99%